Pendugaan, Biomassa Dan Karbon Tanaman Jati Hutan Rakyat DalamMengabsorsi Karbondioksida (CO 2 ) Desa Kare Kecamatan Kare Kabupaten Madiun - Rohmatiah, Ahadiati; Lukito, Martin (JURNAL AGRI-TEK, 2015)
Forests as a producer of environmental services have the potential to reduce carbon dioxide in the atmosphere through photosynthesis. Carbon dioxide exceeded the threshold in the atmosphere can cause the greenhouse effect resulting in global warming is increasing. The research was conducted to find estimation, biomass and carbon forest plants Teak on community forest is in absorbs carbon dioxide (CO 2 ) Developed extensively in Madiun district, and precisely in the village Kare of the sub-District Kare. This research was conducted using sample plots rectangular with an area of 1 ha. Determining the location of the plot is determined by stratified random sampling in areas that have been determined in advance. Results obtained: Estimation of potential stand up for the People's Teak volume on the identity of the community forest village Kare land area of 3154.7 m3. content of Biomass Teak Community forest Village Kare average of 266.80 kg per tree or 50% of average The average weight of the wet conditions. Size Teak Forests People 38.39 Ha as much as 631 stems, the total biomass potential stand Teak is 6462.67 tons. Or when the state average per hectare biomass of 168.35 tons/hectare.Potensi carbon content in biomass conversion method average of 131.31 kg/ tree carbon. With the realization of the plant 24.222 trees or an area of 38.39 hectares, the total potential carbon content is 3,180.71 tons of Carbon. When converted into units of volume per hectare ranges between 84 175 tons of carbon per hectare. The composition of the carbon content of each component of the tree is also different, which is the highest in the stem component, followed by branches, roots, and leaves. The amount of CO 2 sequestration potential Teak Community Forest influenced by the leaf's ability to absorb CO 2 in the photosynthesis process, when converted to the number of plants was 24.222. The tree is about 11 656 tons of CO 2 . Biomass and Carbon content relationship with (DBH) is a model of power with WT = 0.04562.25 for biomass and DBH, CT = 0.0472 DBH 2,233 for carbon. Keywords: Global warming Farm Forestry, Biomass, Carbon